Porphyrins Anchored onto Colour Catcher®: Photoactive Material for the Conversion of Amines into Imines and Aldehydes into Carboxylic Acids - Dr. Caterina Damiano; Matteo Cavalleri; Prof. Corrado diNatale'; Prof. Roberto Paolesse; Prof. Emma Gallo (ChemistryEurope, 2023)
Abstract A new photoactive material was obtained by the heterogenization of zinc(II) porphyrin onto cellulose‐based Colour Catcher® sheet. The so‐obtained Zn(porphyrin)@CC material performed very well in activating molecular oxygen in the photooxidative coupling of amines to imines and the photooxidation of aldehydes to corresponding acids in the presence of white light. The high eco‐compatibility of the solid support, the chemical stability of the photoactive material and the mild experimental conditions applied confer a very good sustainability to the procedure and open the doors to a larger employment of Colour Catcher®‐based porphyrin material in reactions mediated by light.